2008
DOI: 10.1523/jneurosci.0987-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Scenes Unseen: The Parahippocampal Cortex Intrinsically Subserves Contextual Associations, Not Scenes or Places Per Se

Abstract: The parahippocampal cortex (PHC) has been implicated in both place/scene processing and episodic memory. We proposed that this region should instead be seen as intrinsically mediating contextual associations and not place/scene processing or episodic memory exclusively. Given that place/scene processing and episodic memory both rely on associations, this modified framework provides a platform for reconciling what seemed like different roles assigned to the same region. Comparing scenes with scenes, we show her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
178
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(196 citation statements)
references
References 45 publications
13
178
3
2
Order By: Relevance
“…A set of ROIs (PHC, RSC, and MPFC) that we had identified a priori based on activations of contextual association processing in previous studies (8,10,27) showed significantly greater activation for the SCA > WCA contrast in this experiment, replicating the previous studies (Fig. S1).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…A set of ROIs (PHC, RSC, and MPFC) that we had identified a priori based on activations of contextual association processing in previous studies (8,10,27) showed significantly greater activation for the SCA > WCA contrast in this experiment, replicating the previous studies (Fig. S1).…”
Section: Resultssupporting
confidence: 87%
“…Moreover, the anatomical regions between which MEG phase locking was enhanced for the SCA vs. WCA objects are consistent with a host of fMRI studies exploring the neural substrates of contextual association processing (8,10,17,27,56). They also overlap substantially with the default mode network, as discussed in detail in Bar et al (68).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Hence, we take it to reflect continuing mismatch between the internal motor model's expectations and perception, which is increased if the original internal model was highly habituated. The parahippocampal cortex has been associated with topographical learning (Aguirre, Detre, Alsop, & D'Esposito, 1996), scene processing (Epstein & Kanwisher, 1998) and the association of scenes and locations with objects (Bar, Aminoff, & Schacter, 2008;Sommer, Rose, Gläscher, Wolbers, & Büchel, 2005).…”
Section: Solidity Exerts Prolonged Influencementioning
confidence: 99%
“…6C). Given the ubiquitous 648 involvement of this specific brain area in the processing of contextual information needed for 649 successful scene recognition (Bar and Aminoff, 2003;Bar et al, 2008;Kveraga et al, 2011), we 650 interpreted our new results as reflecting similar mechanisms. The linear trend found in this 651 region during accumulation of evidence prior to recognition (see also Schettino et al, 2011) is 652…”
Section: Emotion-dependent Monotonic Accumulation Of Perceptual Evidementioning
confidence: 82%